2018
DOI: 10.3233/bmr-169709
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of musculoskeletal pain distribution, quality of life and hopelessness level in mothers with disabled children in different ambulation levels

Abstract: The risk of musculoskeletal pain, participation in daily life and hopelessness level in the mothers increased as the ambulation level of the disabled children decreased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
1
11
0
5
Order By: Relevance
“…On the other hand, pain complaints can be directly related to the provision of full-time care. According to the results of a study carried out with 177 mothers of children with some type of disability that aimed to analyze how much the childs ability to walk is related to the presence of musculoskeletal pain, including the frequency and severity of pain on the mothers back, shoulders and elbows, significantly increased as the childs level of walking decreased (p<0.05) ( 25 ) . Therefore, the present research is based on the perspective that, when the couple lives a synchronized experience, the provision of care is shared, minimizing possible pain resulting from physical effort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, pain complaints can be directly related to the provision of full-time care. According to the results of a study carried out with 177 mothers of children with some type of disability that aimed to analyze how much the childs ability to walk is related to the presence of musculoskeletal pain, including the frequency and severity of pain on the mothers back, shoulders and elbows, significantly increased as the childs level of walking decreased (p<0.05) ( 25 ) . Therefore, the present research is based on the perspective that, when the couple lives a synchronized experience, the provision of care is shared, minimizing possible pain resulting from physical effort.…”
Section: Discussionmentioning
confidence: 99%
“…Spearman's correlation between parental mutuality and QoLRH domains. Ribeirão Preto, SP, Brazil,[2018][2019] …”
mentioning
confidence: 99%
“…In a study that Telci et al [20] conducted, musculoskeletal pain was observed in mothers with disabled children and this situation was found to affect the quality of life of the mothers negatively.…”
Section: Discussionmentioning
confidence: 99%
“…Among other things, the following links have been shown: between the mother’s depression and the presence of cerebral palsy in the child [ 11 ]; depression of the mother and Down’s syndrome in the child [ 12 ]; depression, anxiety, and suicidal thoughts in the mother and the disability of the child [ 13 ]; and PTSD symptoms in the mother and autism of the child [ 14 ]. Health problems and the disability of the child are also associated with somatic diseases and chronic pain, with musculoskeletal disorders being the most commonly reported in mothers of children with physical disabilities [ 15 , 16 ]. Authors also report deteriorations in the quality of life associated with physical (somatic) pain in mothers of children with congenital heart defects [ 17 ], mothers of children with perinatal shoulder plexus paralysis [ 18 ], mothers of children hospitalized for cancer [ 19 ], and mothers of children with cerebral palsy [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Available research suggests that the occurrence of pain in different regions of the body is linked to poor SRH [ 39 ]. At the same time, available research results suggest that the illness and disability of the child is related to an increased risk of pain in the mother and worse quality of life related to physical pain [ 15 , 16 , 18 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%